The Super Thermal Conductivity Model for High-Temperature Heat Pipe Applied to Heat Pipe Cooled Reactor - Guo, Yuchuan; Su, Zilin; Li, Zeguang; Wang, Kan (Frontiers in Energy Research, 2022)
Differing from the traditional Pressurized Water Reactor (PWR), heat pipe cooled reactor adopts the high-temperature heat pipes to transport fission heat generated in the reactor core. Therefore, the basis of coupling calculation on this type of reactor system is to have a suitable model for high-temperature heat pipe simulation. Not only is it required that this model can well describe the transient characteristics of heat pipe, but it should be simple enough to reduce the computational resource. In this paper, the super thermal conductivity model (STCM) for high-temperature heat pipe is proposed for this purpose. In this model, heat transport of vapor flow is simplified as high efficiency heat conductance. Combined with the network method, the evaporation rate, the condensation rate, and the flow rate in the wick region can be preliminarily obtained. Using recommended equations to calculate the heat transfer limitation, this model can realize the safety judgment of heat pipe. The heating system for high-temperature heat pipe is established to validate this model. The heating experiments with different heating powers is tested. Then, this model is applied on the numerical calculation of Kilowatt Reactor Using Stirling TechnologY (KRUSTY) reactor. In the steady state calculation, the results show that the temperature distribution on contact surface between fuel and heat pipe is nonuniform, which will lead to higher peak temperature and temperature difference for the reactor core. In the transient calculation, the load-following accident is chosen. Comparing with the experimental results, the applicability of the proposed model on heat pipe cooled reactor is verified. This model can be used for heat pipe cooled reactor simulation.